Analysis of the stages of psychological preparation of transplant coordinators (as part of the implementation of the bulk program) - A. P. Poplavskaya (Transplantation and artificial organs, 2020)
This article presents an analysis of the stages of psychological training of future transplant coordinators within the framework of the implementation of the first ZMAPO Transplant Coordinator Program. The introduction of the newly developed program for the training of future transplant coordinators has reflected some of the complexities of the psychological and pedagogical process: first, a lack of purely psychological knowledge and skills, certain problems of mastering new theoretical material, certain difficulties in overcoming barriers to communication. But all this was offset by a desire to get new interesting information, a desire to learn something new, and to develop skills for direct dialogue with potential donors and their relatives.